The milk of dreams = Il latte dei sogni: Biennale arte 2022 - Biennale di Venezia (59e : 2022 : Venise, Italie); Alemani, Cecilia (La Biennale di Venezia, 2022)
The colossal two-part catalog accompanying the 2022 biennial’s ambitious exploration of metamorphosis, as imagined by 213 artists from across the world Named after a children’s book by Surrealist artist Leonora Carrington, the 59th Venice Biennale takes Carrington’s fey creatures, along with other figures of transformation, as companions on an imaginary journey through the metamorphoses of bodies and slippery definitions of humanity. Volume I of this two-part publication addresses the conceptual basis of The Milk of Dreams, as developed by curator Cecilia Alemani, and further elaborates upon its thematic threads. Each artist from the 2022 Biennale is introduced by way of a critical text and an iconographic apparatus. The volume includes Alemani’s original exhibition texts and a plethora of original essays by some of today’s most cutting-edge thinkers and writers, with conversations and reprinted texts concerning the exhibition: the representation of bodies and their metamorphoses, the relationship between individuals and technologies, and the connection between bodies and the earth. Volume II of the catalog presents the participating countries and the collateral events of the biennale; its lavishly illustrated texts explore the various projects on display in Venice. Artists include: Sophia Al-Maria, Josephine Baker, Djuna Barnes, Jadé Fadojutimi, Nan Goldin, Robert Grosvenor, Tishan Hsu, Jacqueline Humphries, Allison Katz, Kapwani Kiwanga, Barbara Kruger, Hannah Levy, Liliane Lijn, Candice Lin, Precious Okoyomon, Akosua Adoma Owusu, Elle Pérez, Aki Sasamoto, Sable Elyse Smith, Kaari Upson, Andra Ursuta, Cecilia Vicuña, Marianne Vitale, Meta Vaux Warrick Fuller and Laura Wheeler Waring.
Keywords: art contemporain; arts; arts visuels et médiatiques; corps; cours; discipline; har4600; histoire de l'art; premier cycle; thématiques

Corps vivante - Delporte, Julie (Éditions Pow Pow, 2022)
"En 1990, Julie Delporte n'a encore jamais vu de butch, mais sa tante préférée chasse et fume le cigare. Presque vingt ans plus tard, elle publie un livre sur Tove Jansson dans lequel elle raconte avec joie que cette artiste finlandaise est la première femme à qui elle s'identifie, seulement elle était lesbienne et pas Julie. À 35 ans, après avoir surligné de toutes les couleurs son exemplaire de La pensée straight de Monique Wittig, Julie Delporte arrête de porter des robes et prend son avenir en main. Dans ce roman graphique qui fait suite à Moi aussi je voulais l'emporter, l'autrice retrace l'histoire de sa sexualité. Une histoire marquée par la violence malheureusement trop banale des agressions, comme par celle des clichés et des injonctions liés à une culture de la performance et de l'hétéronormativité."--
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; 2020-2029; LGBTQIA2+; amériques; approches et analyses; arts; arts visuels et médiatiques; autofiction; bande-dessinée; canada; corps; cours; discipline; europe; france; har4600; identités LGBTQIA2+; point de vue situé; premier cycle; périodes historiques; queer; québec; roman graphique; régions géographiques; sexualité; thématiques; violences; études littéraires